PROBLEMATIKA KURIKULUM DAN PEMBELAJARAN PENDIDIKAN BERKARAKTER - Husnayani, Rahimah; Hasanah Usnur, Uswatun (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
The curriculum plays an important role in creating a good and useful future generation for the nation and state. Creating young men and women who have the characteristics of being responsible, creative, innovative, and who are experts. The curriculum is the heart of the school and the school is the heart of society and society is the heart of a country and nation. So that the nation will progress if it has human resources of high quality, character and quality. However, curriculum development often finds many problems that require solutions. This study aims to identify problems with curriculum and learning in research character education using literature review methods. From the results of the study, it was found that there is a problem with character education curriculum and learning, namely that the formulation of the character education curriculum is still under the interests of group politics. The educational curriculum also overlaps with the curriculum for citizenship education, Pancasila education and religious education. Meanwhile, the problem of character education learning boils down to methods, media, an educational environment that is not conducive, and the loss of role models from parents.